Analysis of Dominant Factors Affecting Reading Delay Reviewed from Internal and External Factors of Students - I Gusti Agung Ayu Kirana Dewi; Ni Ketut Suarni; I Gede Margunayasa (South Sulawesi Education Development (SSED), 2024)
Education is the basis for a child's development and life in the future so that every child has various abilities and skills that are useful for the future. At the base of education there are several activities, one of which is reading. The most important ability for children is reading. The problem in this research is the reading delays experienced by high class students. The role of the teacher must be able to plan reading learning well so that students are able to make it a habit as something very interesting, and can be created through language games in teaching reading to students. By collecting library data from various trusted sources using the literature study method, it can be seen that there are several factors that cause students' reading delays. This research analyzes the forms of internal and external factors that cause sixth grade students to experience reading delays. The data collection technique used is data collected from various sources and the results of this research only apply to the cases investigated. This shows that reading delays are caused by a lack of interest in reading in sixth grade elementary school students in the low sense. From the level of student access to libraries, very few do. Students cannot read because they do not have reading knowledge. Factors that influence students' reading delays are internal and external factors, although not all students experience difficulties in beginning reading. It is hoped that with this research teachers can train students in reading